2007
DOI: 10.1097/inf.0b013e318124aa1a
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease in Korea, 2003–2005

Abstract: The average annual rate of incidence, 105.0/100,000 in children <5-year-old is the second highest reported rate in the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 8 publications
8
30
3
Order By: Relevance
“…It has been reported that boys have 1.5 times higher incidence than girls in Korea (Park et al 2007(Park et al , 2010. In consideration of the higher incidence of KD in males, we analyzed the data separately by sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that boys have 1.5 times higher incidence than girls in Korea (Park et al 2007(Park et al , 2010. In consideration of the higher incidence of KD in males, we analyzed the data separately by sex.…”
Section: Discussionmentioning
confidence: 99%
“…There are several lines of evidence to support a genetic contribution to disease susceptibility and outcome. The incidence of KD is 12-19 times higher in Japanese and Koreans than in Caucasians Park et al 2007;Holman et al 2003), and it is maintained in JapaneseAmerican residents in the United States (Holman et al 2005). The risk of KD occurrence in twins and siblings of an index case is higher than that in the normal population (Fujita et al 1989;Harada et al 1986); and the incidence of KD in children whose parents have a history of KD is twice as high as that in the general population (Fujita et al 1989;Uehara et al 2003).…”
Section: Introductionmentioning
confidence: 96%
“…The incidence of Kawasaki disease was observed to be highest in Asians, intermediate in non-Hispanic African-Americans and Hispanics, and lowest in Caucasians (32.5, 16.9, 11.1, and 9.1 per 100,000 children less than 5 years old, respectively) [3]. The incidence rate in Korea was 105 per 100,000 children less than 5 year old [4]. Treatment with intravenous immunoglobulin (IVIG) abrogates the inflammation in approximately 80% of affected individuals and reduces the aneurysm rate to less than 5% [5].…”
Section: Introductionmentioning
confidence: 95%
“…The highest incidence rate of Kawasaki disease is seen in Japan and in a four-year epidemiological survey between 1999 and 2002, the average incidence rate was 137.7 cases per 100000 children under 5 years of age. In an epidemiological survey in Korea, the incidence rate between 2003 and 2005 was approximately 105 cases per 100000 children under 5 years of age, a rate that was the second highest in the world after Japan (270). …”
Section: Prefacementioning
confidence: 99%